Metabolic Syndrome and Prediabetes Among Yemeni School-Aged Children - Saeed W; AL-Habori M; Saif-Ali R; Al-Eryani E (Diabetes, Metabolic Syndrome and Obesity, 2020)
Walid Saeed, Molham AL-Habori, Riyadh Saif-Ali, Ekram Al-Eryani Department of Biochemistry and Molecular Biology, Faculty of Medicine and Health Sciences, University of Sana`a, Sana`a, YemenCorrespondence: Molham AL-Habori Email malhabori@hotmail.comPurpose: In view of the high rate of obesity and physical inactivity as well as the rising incidence of Type 2 DM among children in the neighboring Gulf countries and Middle East region; the aim of this study was, therefore, to determine the prevalence of metabolic syndrome (MetS) and prediabetes in Yemeni school-aged children.Patients and Methods: In this study, 1402 school children aged 12– 13 years old (grade 7) were recruited from public schools in the capital Sana’a during the period April–May 2013. Anthropometric measurements and BP were recorded and BMI was calculated. Fasting venous blood (5 mL) was collected for biochemical analysis including FBG, HbA1c, insulin and lipids profile. Insulin resistance (HOMA-IR) and β-cell function (HOMA-β) were calculated.Results: The prevalence of prediabetes (as defined by impaired fasting glucose) and MetS (as classified by the IDF 2007) were 0.86% and 0.5%, respectively. Our results also showed 5.21% and 20.26% of the children to have two or one factor(s) of the MetS criteria fulfilled, respectively, with low HDL-c (17%) being the most prevalent MetS component, followed by metabolic glucose (8%), raised TG (5.3%), DBP (1.4%), and high WC (0.5%). Moreover, the prevalence of overweight and obesity was 4.2% and 2.8%, respectively; and about 1.2% of children had abnormal high insulin levels. Children with impaired fasting glucose (IFG) had increased HOMA-IR (p = 0.016) and SBP (p = 0.042) and decreased HDL-c (p = 0.034) and HOMA-β (p < 0.001); whereas obese children had increased WC (p < 0.001) and TG (p = 0.049).Conclusion: The main finding of this study is that Yemeni children are at potential risk of obesity, metabolic syndrome and prediabetes despite their low prevalences. These results highlight the need for early identification and close monitoring of children at risk of later Type 2 DM as an important primary care strategy that can effectively prevent or delay the onset of such condition.Keywords: metabolic syndrome, prediabetes, obesity, insulin resistance, school-aged children